Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I have the following equation to calculate its derivative:

$$f(x) = e^{3x}(\sin(x)+\cos(x))$$

I used the product rule and I got this answer:

$$e^{3x}(\sin(x)+\cos(x))+e^{3x}(\cos(x)-\sin(x))$$

But the answer at the end of the book is:

$$3e^{3x}(\sin(x)+\cos(x))+e^{3x}(\cos(x)-\sin(x))$$

I am scratching my head to find where that $3$ came from. I think I have to use chaing rule here as well, but I am not sure to take which part of equation as $z$.

share|improve this question
4  
The derivative of $e^{3x}$ is $3e^{3x}$. –  azarel Apr 12 '12 at 18:31
    
You could also simplify the answer further by factoring out $e^{3x}$ and combining like terms. –  Mike Apr 12 '12 at 20:06
add comment

1 Answer

up vote 2 down vote accepted

Let $g(x)=e^{3x}$ and $h(x)=\sin(x)+\cos(x)$.Then $f(x)=g(x)\cdot h(x)$. The product rule states $f'(x)=g'(x)h(x)+g(x)h'(x)$.In our case $$(e^{3x})'(\sin(x)+\cos(x))+(e^{3x})(\sin(x)+\cos(x))'=3e^{3x}(\sin(x)+\cos(x))+e^{3x}(\cos(x)-\sin(x))$$

Watch out that $ (e^{3x})'=3e^{3x}$. That's because $e^{3x}=e^{z}$ where $z=3x$. Therefore $\frac{de^z}{dx}=\frac{de^z}{dz}\frac{dz}{dx}=e^z\cdot z'(x)$. Substituting back, we got: $\frac{de^{3x}}{dx}=e^{3x}\cdot (3x)'=3e^{3x}$

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.